The frequency of acute atherosis in normal pregnancy and preterm labor, preeclampsia, small-for-gestational age, fetal death and midtrimester spontaneous abortion*. (22nd November 2015) - Kim, Yeon Mee; Chaemsaithong, Piya; Romero, Roberto; Shaman, Majid; Kim, Chong Jai; Kim, Jung-Sun; Qureshi, Faisal; Jacques, Suzanne M.; Ahmed, Ahmed I.; Chaiworapongsa, Tinnakorn; Hassan, Sonia S.; Yeo, Lami; et al.
Abstract: Objective : Acute atherosis is characterized by subendothelial lipid-filled foam cells, fibrinoid necrosis and perivascular lymphocytic infiltration. This lesion is generally confined to non-transformed spiral arteries and is frequently observed in patients with preeclampsia. However, the frequency of acute atherosis in the great obstetrical syndromes is unknown. The purpose of this study was to determine the frequency and topographic distribution of acute atherosis in placentas and placental bed biopsy samples obtained from women with normal pregnancy and those affected by the "great obstetrical syndromes". We also examined the relationship between acute atherosis and pregnancy outcome in patients with preeclampsia. Material and methods : A retrospective cohort study of pregnant women who delivered between July 1998 and July 2014 at Hutzel Women's Hospital/Detroit Medical Center was conducted to examine 16 345 placentas. Patients were classified into the following groups: (1) uncomplicated pregnancy; (2) spontaneous preterm labor (sPTL) and preterm prelabor rupture of membranes (PPROM); (3) preeclampsia; (4) gestational hypertension; (5) small-for-gestational age (SGA); (6) chronic hypertension; (5) fetal death; (6) spontaneous abortion and (7) others. A subset of patients had placental bed biopsy. The incidence of acute atherosis was compared among the different groups. Results : (1) The prevalence of acute atherosis in uncomplicated pregnancies was 0.4% (29/6961) based upon examination of nearly 7000 placentas; (2) the frequency of acute atherosis was 10.2% (181/1779) in preeclampsia, 9% (26/292) in fetal death, 2.5% (3/120) in midtrimester spontaneous abortion, 1.7% (22/1, 298) in SGA neonates and 1.2% (23/1, 841) in sPTL and PPROM; (3) among patients with preeclampsia, those with acute atherosis than in those without the lesion had significantly more severe disease, earlier onset, and a greater frequency of SGA neonates ( p  < 0.05 all) and (4) the lesion was more frequently observed in the decidua (parietalis or basalis) than in the decidual segment of the spiral arteries in patients with placental bed biopsies. Conclusions : Acute atherosis is rare in normal pregnancy, and occurs more frequently in patients with pregnancy complications, including preeclampsia, sPTL, preterm PROM, midtrimester spontaneous abortion, fetal death and SGA.